Radiofrequency catheter abilation of midseptal and anteroseptal accessory atrioventricular pathways in pediatric patients - Prorok, S. Y.; Doronin, O. V.; Meshkova, M. S. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Method of discrete exposure to radiofrequency current was used in 46 patients with midseptal and anteroseptal accessory atrioventricular pathways. No cases of iatrogenic AV-block were observed in the immediate and late periods. The overall effectiveness of the method is 73,3%. Our approach in treating this group of patients is safe and perfectly acceptable alternative to chronic antiarrhythmic therapy in children.